Environmental psychology and human well-being : effects of built and natural settings - Devlin, Ann Sloan, 1948- (Academic Press, 2018)
Environmental Psychology and Human Well-Being: Effects of Built and Natural Settings provides a better understanding of the way in which mental and physical well-being is affected by physical environments, along with insights into how the design of these environments might be improved to support better health outcomes. The book reviews the history of the field, discusses theoretical constructs in guiding research and design, and provides an up-to-date survey of research findings. Core psychological constructs, such as personal space, territoriality, privacy, resilience, stress, and more are integrated into each environment covered.